ANALISIS PENGARUH KEPERCAYAAN, KEPUASAN DAN PENAWARAN TERHADAP DAYA SAING KONTRAKTOR KECIL DAN PERORANGAN - Gyan Agye Try Krystyan; Mawardi Amin; Agus Suroso (LPPM Universitas Negeri Jakarta, 2025)
Abstract In 2022, Indonesia was home to 24,236 construction companies, with contractors dominating the sector, comprising 21,786 firms or 89.86% (Badan Pusat Statistik, 2022), The large number of contracting companies has led to intense competition. Several factors enable contractors to compete, including owner trust, owner satisfaction, and pricing offers. This study aimed to analyze the impact of trust and satisfaction on contractor competitiveness, with pricing offers serving as an intervening variable. In the competitive Indonesian construction industry, understanding the factors that affect contractor competitiveness is crucial as it enhances the effectiveness of competitive strategies. This research employed a quantitative method with a survey approach. Data were collected through questionnaires from project owners, and path analysis was utilized to test the relationships between the research variables with the aid of SMART-PLS data processing tools. The findings indicate that trust affects competitiveness through pricing offers as an intervening variable, whereas satisfaction directly affects competitiveness without the mediation of pricing offers.